Hierarchical Octahedral Na2MnFe(CN)6 and Na2MnFe(CN)6@Ppy as Cathode Materials for Sodium‐Ion Batteries. Issue 4 (31st March 2017) - Hu, Fangdong; Li, Lin; Jiang, Xiaolei
Abstract: The Na2 MnFe(CN)6 is successfully synthesized by a simple co‐precipitation method, and then coated with conducting polymers (PPy) on the surface of Na2 MnFe(CN)6 particle. Interestingly, Na2 MnFe(CN)6 and Na2 MnFe(CN)6 @PPy both show hollow octahedral hierarchical structures with nanometer‐sized subunits. Na2 MnFe(CN)6 @PPy exhibits a discharge capacity of 107 mAhg −1 after 150 cycles at a current density of 10 mAg −1 . It can still remain 65 mAhg −1 even the current density is increased to 200 mAg −1 . This superior electrochemical property could be ascribed to unique hierarchical architecture as well as improved electronic conductivity. Abstract : The Na2 MnFe(CN)6 was successfully synthesized by a simple co‐precipitation method. Interestingly, Na2 MnFe(CN)6 shows hollow octahedral hierarchical structures with nanometer‐sized subunits. Then, conducting polymers (PPy) were coated on the surface of Na2 MnFe(CN)6 particles, and Na2 MnFe(CN)6 @PPy also presented hollow octahedral hierarchical structure.